Designerly Ways to Theoretical Insight: Visualisation as a means to explore, discuss and understand design theory - Bang, Anne Louise; Friis, Silje Alberthe Kamille; Gelting, Anne Katrine Gøtzsche (Design and Technology Education: An International Journal, 2015)
This paper set out to investigate how design students learn from visualising theory in design education. The exploration rests on the assumption that the application of tools and techniques from design practice supports design students with an entrance to the theoretical part of the field. The paper is based on teaching experiences from an MA course in design methodology at Design School Kolding where we use visualisation as a tool to discuss, explore and understand design theory. To throw light on the question, student evaluations and feedback has been included together with a classification of the material from one visualisation exercise. In addition, theories for how to understand designerly ways of knowing and constructing knowledge have been applied as tools to think with in the discussion. The educational approach where design students read, analyse, and visualise theory, appears to be beneficial to the students’ learning process for a number of reasons, which will be discussed in the paper. The main findings indicate that visualising theory is beneficial because it applies a type of practice that the students are familiar with, and supports the construction of new knowledge, by allowing the students to express information and concepts in ways that are personally meaningful to them.